2011
DOI: 10.1007/s10608-011-9357-z
|View full text |Cite
|
Sign up to set email alerts
|

The Predictors and Contents of Post-Event Processing in Social Anxiety

Abstract: The present study investigated the factors that influence the likelihood that individuals engage in postevent processing (PEP)-the act of engaging in a detailed, negative, and self-focused review following social situations. This study also examined the cognitive contents of PEP in a nonclinical sample (N = 40). Participants undertook both a 5-min speech and conversation and then completed measures assessing cognitions, behaviours, and physiological processes that occurred during each task. Twenty-four hours l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 66 publications
3
31
0
Order By: Relevance
“…The present study extends the growing literature on cognitive-behavioral features of anticipatory and post-event processing in SA (e.g., Edwards, Rapee, & Franklin, 2003;Gaydukevych & Kocovski, 2012;Kashdan & Roberts, 2007;Makkar & Grisham, 2011;Mellings & Alden, 2000;Morgan & Banerjee, 2008;Van Boven & Ashworth, 2007;Vassilopoulos, 2005) by directly comparing the nature and impact of anticipatory images and memories with those generated during post-event processing of an anxiety-provoking social event. While previous studies have investigated retrospectively-or typically-occurring mental images in social situations (e.g., Hackmann et al, 2000;, the current study examined these phenomena in the context of an in vivo anxiety-provoking social task, thereby helping to mitigate the potential threat of reporting biases.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The present study extends the growing literature on cognitive-behavioral features of anticipatory and post-event processing in SA (e.g., Edwards, Rapee, & Franklin, 2003;Gaydukevych & Kocovski, 2012;Kashdan & Roberts, 2007;Makkar & Grisham, 2011;Mellings & Alden, 2000;Morgan & Banerjee, 2008;Van Boven & Ashworth, 2007;Vassilopoulos, 2005) by directly comparing the nature and impact of anticipatory images and memories with those generated during post-event processing of an anxiety-provoking social event. While previous studies have investigated retrospectively-or typically-occurring mental images in social situations (e.g., Hackmann et al, 2000;, the current study examined these phenomena in the context of an in vivo anxiety-provoking social task, thereby helping to mitigate the potential threat of reporting biases.…”
Section: Discussionsupporting
confidence: 54%
“…Although both anticipatory and post-event processes and their roles in the maintenance of SA are theorized to play prominent roles in the maintenance of SA symptoms (e.g., Clark & Wells, 1995;Hofmann, 2007;Rapee & Heimberg, 1997) and extensive previous research has helped elucidate the nature of both types of processes (see Brozovich & Heimberg, 2008;Vassilopoulos, 2005), few studies have examined the relation between images or memories and these processes (Edwards, Rapee, & Franklin, 2003;Makkar & Grisham, 2011;Mellings & Alden, 2000;Morgan & Banerjee, 2008), and to our knowledge, no previous studies have directly compared the attributes of images and associated autobiographical memories retrieved during anticipation versus post-event processing.…”
mentioning
confidence: 99%
“…Moreover, the Wong and Moulds () study (described earlier) found that analytical rumination was associated with a decrease in UBs, t (21) = 2.53, p = .02, d = 0.32, compared with an experiential rumination task, t (21) = −0.18, p = .86, d = 0.01, in high socially anxious individuals, F (1, 42) = 5.45, p = .02, partial η 2 = .12. Finally, Makkar and Grisham () found the total SBSA scale was a unique predictor of the post‐mortem following a speech task, β = .46, t (26) = 2.08, p < .05, but not following a conversation task. It should be noted that the latter study ran a regression analysis with 12 predictors on a sample of 40 individuals, which may have limited its robustness and power.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 10 metacognitive belief studies, four were conducted in the United Kingdom (Dannahy & Stopa, ; Field & Cartwright‐Hatton, ; Gkika & Wells, ; Wells & Carter, ), two in the United States (Fergus, Valentiner, McGrath, Gier‐Lonsway, & Jencius, ; Fisak & Hammond, ), two in Australia (McEvoy & Perini, ; Wong & Moulds, ), one in Norway (Nordahl, Nordahl, & Wells, ), and one in Greece (Vassilopoulos et al, ). Of the 13 social belief studies, 11 were conducted in Australia (Makkar & Grisham, , ; Wong, McEvoy, & Rapee, ; Wong & Moulds, , , , , , ; Wong et al, , ), one in Belgium and Switzerland (Heeren et al, ), and one in the United States (Holzman et al, ). Four studies on metacognitive beliefs (Fergus et al, ; McEvoy & Perini, ; Nordahl et al, ; Wells & Carter, ) and two on social beliefs (Wong et al, , ) used clinical samples.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the previous studies, other studies have highlighted the importance of other predictors. Makkar and Grisham () showed with an unselected sample of participants that in general a speech task led to more post‐event processing compared to a conversation task. In terms of specific predictors, Makkar and Grisham () demonstrated that for the speech task, depression levels, trait social anxiety, and state negative social‐evaluative beliefs positively predicted level of post‐event processing in the subsequent 24 hr.…”
Section: Empirical Findings From the Extant Literaturementioning
confidence: 99%